Pernikahan Dini Dalam Hukum Perkawinan di Indonesia - Mardiono, Eko (Sunan Kalijaga State Islamic University & The Asia Foundation, 2009)
Contemporary Indonesians witness the rise of the popularity of marriage of the minors, despite the application of the Indonesian Marriage Law no 1/1974 that forbids child marriages for decades. The enactment of the Law decades ago was meant to be a social engineering mean to erase the practice of child marriage with social compromises. Recent research in medical studies show that there is significantly high risk for young women under 18 years old who do sexual intercourse to be infected with servick cancer. Many other research on child marriage using psychological and social approaches also suggest that actors of child marriage are of high risk of suffering from social and psychological troubles. Now, what can we do with the Indonesian Marriage Law that still endorse marriage for girls under 18 years old? This paper discusses the issues from different perspectives.